Chronic constipation among community-dwelling older people in the East Coast region of Peninsular Malaysia - Wahab, Patimah Abdul; Kadir, Azidah Abdul; Lee, Yeong Yeh; Ali, Siti Hawa; Yusoff, Dariah Mohd (Makara Journal of Health Research, 2019)
Background: This study aimed to investigate the prevalence, symptoms, and factors associated with chronic constipation among community-dwelling older people in the East Coast region of Peninsular Malaysia. Methods: A cross-sectional study was conducted in four selected health clinics using stratified cluster sampling. A face-to-face interview was carried out among the elderly outpatients, in order to complete a structured questionnaire. Results: A total of 400 participants were included in the study. The mean age was 68.7 ± 6.4 years, and 55% of the cohort were women. The prevalence of chronic constipation was 32.3% among the sample population. The most common symptom was “sensation of incomplete evacuation” (63.6%), and none of the participants reported having “less than three defecations per week,” “straining,” or “lumpy or hard stool.” Educational level (p = 0.005), number of defecations per week, stool form, time spent for defecation, and abdominal bloating were significantly associated with chronic constipation (p < 0.001). Conclusion: Chronic constipation was common in older people and associated with a low educational level. Recognition of symptoms was predominantly based on clinical features of constipation and will require the healthcare providers to consider these factors in their routine assessment of older people.